The Correlation between COVID-19 knowledge and stress levels on Students of NCIPS Junior High School Kupang, 2021 - Martins, Graciela Maria Dolores; Hutasoit, Regina; Lidia, Kartini (Universitas Nusa Cendana, 2023)
Abstract: The knowledge of COVID-19 is prime important for community include adolescence in order to enable them to deal with stress, as well as strength for adaptation to the COVID-19. Purposes : This research was conducted with the intention to understand if there is any correlation between knowledge of the students at SMP NCIPS, Kupang about COVID-19 towards the level of stress. Methods: The research utilized an analytical cross-sectional study approach, involving 42 students from 49, who completed questionnaires on COVID-19 knowledge and perceived stress scales, and analyzed using Somers' D correlation test. Results: The findings showed that, out of 42 respondents, 81% of NCIPS Kupang Junior High School students experienced moderate to very high stress, with 47.6% having sufficient knowledge and 38.1% having good knowledge. However, there was no significant correlation between COVID-19 knowledge and stress experienced by student Conclusion: There was no significant correlation (p = 1,000)between the level of knowledge of COVID-19 and the level of stress experienced by students at NCIPS Junior High School, Kupang.